Self-Efficacy of Choosing Delivery Method and Labor Among Pregnant Women in Pars-Abad City - Safieh Kanani; Hamid Allahverdipour (Hamadan University of Medical Sciences, 2014)
Introduction: Self-efficacy is a person's belief on his or her own ability to successfully perform a task. It is one's own ability to cope with stressful situations and implement necessary actions, especially in labor. The aim of this study was to investigate the effect of self-efficacy on choosing delivery method and labor among women. Materials and Methods: This was a cross-sectional and descriptive study. The non-probability sample consisted of 200 primiparous and multipara women in the third trimester of pregnancy recruited from five urban health care centers in Pars-Abad city, Ardebil province, Iran, in 2014. The standard and self-administered questionnaires were used for data collection including demographic variables and self-efficacy of choosing natural vaginal delivery and labor via self-report method. Data analysis was performed using SPSS-21 software by chi-square, Fisher exact test and independent T-test. Results: The mean age of all participants was 25.19 (±4.48). A significant difference was found between spouse education levels, having supplemental insurance and employment status with choosing the delivery method (P < 0.05). Self-efficacy to choose natural vaginal delivery and self-efficacy of labor were associated with parity and choosing the delivery method (P<0.001) the average two types of self-efficacy were higher in multipara women and those who selected natural delivery method. Conclusion: Self-efficacy to choose natural vaginal delivery and labor determies choosing the delivery method and is related to parity. Therefore, it is suggested to focus on self-efficacy in educational interventions to reduce fear of childbirth, especially in primiparous women.